The Influence of the Proximity of Residence to Rice Field Areas and Country Areas Area Industry to Incident Diabetes Mellitus Type 2 - Irvan, Muhammad; Romadhon, Yusuf Alam (Journal La Medihealtico, 2024)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia (high blood glucose levels) due to insulin deficiency, insulin resistance or both. The International Diabetes Federation (IDF) estimates that in the 20-79 age group, there were 463 million people in the world suffering from diabetes mellitus in 2019. Based on data from the Kendal Regency Health Office, in 2021 there were 19,020 people suffering from diabetes mellitus, with a prevalence rate of 2.8% of the total population. People who live in rice fields have a risk factor risk of type 2 diabetes mellitus such as exposure to pesticides as well as not enough activity Physical pollutants from exposure to nitrogen dioxide (NO2), particulate matter (PM2.5) and (PM10) found in industrial areas can cause glucose metabolism disorders and increase HbA1C levels. Study This For analyze influence proximity place stay with rice field area And area area industry on the incidence of type 2 diabetes mellitus in Kendal Regency. This study use analytic observational with design study cross sectional. Technique taking sample Which used is purposive sampling. Analysis univariate And bivariate use test Chi-Square. Got it results Which significant based on test Chi-Square about influence place stay in area rice fields And area industry with the occurrence type 2 diabetes mellitus with p-value as big as 0,000 ( p-value <0.05). Study This show existence influence proximity place stay with rice fields and area area industry to incident type 2 diabetes mellitus in Regency Kendal.